Geopolymer for road grouting reinforcement and preparation method and application thereof
By mixing alkaline thermal activation of powder and coal ash, and mixing with slag powder, kaolin and silicane substances, the problem of cracking material is prone to occur during drying and shrinkage, which improves the pressure resistance and durability Sexuality has achieved environmental and efficient road repair effects.
Patent Information
- Application Number
- CN202411496880.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing polymer grouting materials are prone to cracks during drying and shrinking, and have low compressive strength, making it difficult to meet actual engineering needs.
By adding a mixed alkali solution to the powder ash for high temperature activation, combined with the mix of slag powder and the altitude, adding sirrifice substances and decentralized liquids to prepare high -performance polymers. This method includes steps such as stirring, heating activation, cooling grinding, uniform mixing, and additives.
It improves the pressure resistance of the ground polymer, reduces the dry contraction rate, enhances the high temperature resistance, chemical corrosion and anti -permeability of the material, and is suitable for road grouting and reinforcement, reducing the environmental protection of consumables and craftsmanship.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of geopolymers, and in particular relates to a geopolymer for road grouting reinforcement and a preparation method and application thereof. Background Art
[0002] The rapid development of cities in my country and the surge in the number of vehicles have made "traffic congestion" the most stubborn problem that plagues urban construction and development. Once a road surface is damaged, it will inevitably make the road section impassable, making the already congested traffic even worse, and seriously affecting people's transportation. Therefore, for current urban construction, how to effectively solve the problem of road surface damage and how to quickly repair the road surface are crucial.
[0003] At present, cement grouting material is the commonly used material for road grouting treatment. Its advantages are mature technology and wide application, but it has defects such as high water separation rate and long setting time. Many projects have begun to use geopolymer grouting materials to replace traditional cement. This geopolymer grouting material has the characteristics of low energy consumption and high performance in the production process and has broad application prospects. The active application of geopolymer grouting technology in road maintenance projects can effectively repair damaged roads on the one hand, and further improve the comfort and safety of road surface use on the other hand.
[0004] Studies have shown that the modulus of the activator and the alkali-solid ratio can change the compressive strength of the solidified soil within a certain range, and the compressive strength of the geopolymer solidified soil samples shows a trend of first increasing and then decreasing. The compressive strength of fly ash geopolymer solidified soil is limitedly affected by the modulus of the alkali activator and the alkali-solid ratio. The compressive strength of fly ash geopolymer solidified soil is always low and difficult to meet the needs of actual engineering. The mineral composition of the high-aluminum fly ash used is crystalline minerals such as mullite and corundum and amorphous aluminum silicate minerals. The volcanic ash has poor activity and is difficult to prepare geopolymers by depolymerization-condensation under low alkali or sulfate excitation. The present invention is used to improve the above problems by mixing alkali for activation at high temperature.
[0005] The polycondensation reaction of geopolymers and the evaporation of free water will cause the components to shrink and deform. Under the condition of constraints, cracking is very likely to occur, which also leads to the limitation of the promotion and application of geopolymers. The cracks of geopolymers mainly occur in the drying shrinkage stage. Therefore, slowing down the evaporation and water loss rate of materials in a dry environment and improving the shrinkage resistance of materials are important ways to solve the drying shrinkage cracking of concrete components. Studies have shown that silicon-containing substances can play a pore filling role in the carbonization process of geopolymer recycled concrete, which can effectively reduce the porosity of harmful pores and harmful pores.
[0006] When pouring large volumes of concrete, the exposed surface of the concrete structure often has a large temperature difference. If the temperature changes greatly, or the concrete is exposed to colder air for a long time, the surface temperature will drop rapidly, and the shrinkage of the concrete surface will be constrained by internal forces. This constraint is the tensile strength of the material itself. When this resistance cannot withstand the shrinkage of the concrete, cracks will occur. The dispersion can significantly improve the dispersion stability of solid particles in the liquid medium. Polymer dispersants form an adsorption layer on the surface of the particles, increase the charge on the surface of the particles, thereby increasing the reaction force between the particles and preventing the particles from aggregating and settling. How to prepare the dispersion to reduce the uneven settlement and cracking of geopolymer concrete is the research focus of the present invention. Summary of the invention
[0007] In order to solve the above technical problems, the specific preparation method and application of the present invention are as follows:
[0008] A method for preparing a geopolymer for road grouting reinforcement:
[0009] Add 18-25% mixed alkali solution to fly ash, stir at 500RPM for 20-30min, place it in a muffle furnace, heat it to 600-700℃ at 15℃ / min for 80-90min, cool it to room temperature and grind it to a specific surface area of 280-320m 2 / kg to obtain alkali thermally activated fly ash;
[0010] Alkaline thermally activated fly ash: slag powder: metakaolin are mixed in a ratio of 5:3:2, 2-5% of silane is added thereto and stirred evenly, then the dispersion is added in a material-liquid ratio of 6:4, first stirred slowly at 10-50 RPM for 1 minute, then stirred quickly at 100-200 RPM for 4 minutes, to obtain a high-performance geopolymer;
[0011] The mixed alkali solution is a solution in which tetra-n-butylammonium difluorotriphenylsilicate and sodium hydroxide are mixed in a ratio of 1:3 with a mass fraction of 8-20%.
[0012] The silane material is benzyltriethoxysilane.
[0013] The dispersion liquid is prepared by mixing 0.1-0.5 parts of cellulose ether, 2-5 parts of FDN-C naphthalene water reducer, 0.5-0.8 parts of polyethylene glycol and 600 parts of water, and then adding 2-5 parts of a surfactant to disperse evenly, rotating at 300RPM, heating at 80°C for 40-60 minutes, and then placing it in an ultrasonic cleaning machine for ultrasonic dispersion for 30 minutes, and then placing it at room temperature for 2-3 hours to obtain a dispersion liquid.
[0014] The surfactant is sodium cocoyloxyethyl sulfonate.
[0015] A geopolymer for road grouting reinforcement and a preparation method and application thereof, characterized in that the application includes:
[0016] (1) Divide the construction area according to the defect detection results and design, and set out on site in the construction area according to the designed grouting drilling hole layout diagram, determine the drilling hole location and mark the location with spray paint, and mark the drilling depth;
[0017] (2) Use a 20 mm diameter drill bit to drill holes according to the hole layout. When drilling, keep the drill rig vertical to the road surface to avoid left and right shaking. After the drill rod reaches the designed depth, the drill rod should be pulled up and down to discharge the powder in the hole, and then move to the next hole position and repeat the step;
[0018] (3) After the drilling is completed, check the hole depth. If the depth is not enough, deepen it again to reach the designed hole depth. During the drilling process, use a cleaning tool to clean the powder around the hole, use a special container to hold the powder, and centrally dispose of it after the construction is completed;
[0019] (4) grouting the prepared geopolymer grouting material, with a grouting pressure of 0.6 MPa, a grouting hole spacing of 150 cm, a grouting volume of 70-120 kg / m2, and a grouting depth of 0.8-1.2 m;
[0020] (5) After the grouting is completed, quickly close the grouting hole with a plug, rinse off the grout spilled on the road surface, and clean the road surface;
[0021] (6) After grouting is completed, it must be cured for 6 hours before subsequent paving construction can begin.
[0022] The beneficial effects of the present invention are:
[0023] 1. The present invention discloses a preparation method and application of a geopolymer for road grouting reinforcement. The present invention uses slag, fly ash, metakaolin and alkaline activator as raw materials to develop a geopolymer grouting material suitable for roadbed reinforcement. By activating the fly ash with alkaline high temperature and mixing it with fillers, dispersants and the like, a geopolymer with high compressive strength, high temperature resistance, chemical corrosion resistance, excellent impermeability and low shrinkage is obtained for grouting to repair damaged roads, thereby reducing consumables and making the process environmentally friendly.
[0024] 2. Traditional roads require 14 procedures during the repair process, with high overall costs, long repair time, and great interference to traffic. The grouting technology of the present invention only requires 6 procedures, which saves construction costs and greatly shortens the construction period. The grouting method can deal with many problems such as partial cracks, void filling, and subsidence on the road surface. The grouting technology is used to inject geopolymer grouting materials into the roadbed or semi-rigid pavement base with crack diseases through drilling, which can play a role in reinforcing the roadbed or semi-rigid pavement base and enable industrial waste to be reused. Compared with excavation maintenance, grouting reinforcement technology has the advantages of short construction period, reduced machinery and labor consumption, small impact on traffic and environment, and small public opinion pressure and social impact. Geopolymer slurry has good fluidity, good water retention and volume stability under pressure, high early strength after solidification, and no shrinkage, micro-expansion, etc. Therefore, the present invention uses tetra-n-butylammonium difluorotriphenyl silicate and sodium hydroxide as active activators, and improves the reactivity of high-aluminum fly ash by alkali thermal activation. Under alkali thermal activation conditions, the activator can effectively improve the reactivity of high-aluminum fly ash, so that the mullite phase and corundum phase in the fly ash basically disappear, and promote the transformation of the amorphous phase into sodium aluminosilicate and sodium silicate with higher crystallinity.
[0025] 3. The ionic groups in tetra-n-butylammonium difluorotriphenyl silicate reconstruct the fly ash with OH- to form a layered double hydroxide main plate structure. At the same time, the tetra-n-butylammonium ions and fluoride ions in tetra-n-butylammonium difluorotriphenyl silicate enter the interlayer and reconstruct with Na+ and Ca2+ in the fly ash to form a compound with higher crystallinity. Tetra-n-butylammonium difluorotriphenyl silicate promotes the fly ash-slag geopolymer solidified soil to generate a large amount of (N, C)-ASH and CSH by providing a variety of rich ionic groups, which fill between the particles, making the soil structure have good integrity, the solidified soil has high compressive strength, and the strength, compression and flexural properties of the geopolymer material are increased.
[0026] 4. The present invention optimizes the mix ratio of geopolymers with benzyltriethoxysilane to improve the shrinkage and cracking of geopolymer materials, wherein benzyltriethoxy helps to form a protective film component in the slurry, slowing down the evaporation of water, thereby reducing the risk of drying shrinkage. The internal curing function of benzyltriethoxysilane can compensate for the water loss inside the sample in a dry environment, reduce the polymer coagulation time, and even in a dry environment, optimize the water retention inside the geopolymer material, minimize the evaporation water loss rate, and greatly delay the problem of drying shrinkage and cracking of the geopolymer material.
[0027] 5. Adding benzyltriethoxysilane as a filler can improve the generation of new gels such as calcium silicate and hydrated calcium aluminosilicate. The various generated gels are intertwined and linked to form a gel structure. As the amount of gel generated gradually increases, the free water in the mixed liquid is gradually converted into bound water, and the slurry gradually hardens. Therefore, the addition of benzyltriethoxysilane accelerates the reaction process, shortens the coagulation time of the geopolymer slurry, and ensures the construction quality.
[0028] 6. The present invention selects sodium cocoyloxyethyl sulfonate as a surfactant to increase the water reduction, flow increase and setting reduction effects in the dispersion. By adding additives with setting retardation and water reduction functions, the release of hydration heat can be delayed and the generation of heat can be reduced. The temperature cracks of the concrete are controlled within the minimum range.
[0029] 7. The sodium cocoyloxyethyl sulfonate molecule has two parts, hydrophilic and hydrophobic. This amphiphilic structure enables it to reduce the surface tension in the dispersion and subsequently improve the fluidity of the geopolymer, thereby achieving a flow-increasing effect. The hydroxyl and sulfonic acid groups in the sodium cocoyloxyethyl sulfonate can form more hydrogen bonds with the components in the dispersion, thereby enhancing the adhesion of the subsequent geopolymer material. By adsorbing on the surface of the geopolymer particles, the friction between the particles is reduced, and the viscosity of the slurry is increased while the fluidity is improved, thereby effectively controlling the temperature change of the geopolymer within a minimum range, reducing the shrinkage and stress concentration caused by the temperature difference, and improving the freeze-thaw resistance, thereby greatly reducing the possibility of cracks.
[0030] 8. Sodium cocoyloxyethyl sulfonate can effectively control the distribution of water in the mixture and reduce the evaporation and loss of water. This helps to keep the slurry moist and prevent shrinkage caused by rapid drying. Silane makes the material structure more stable by promoting cross-linking reactions in geopolymers. Such stability can reduce the internal stress caused by uneven shrinkage when the temperature changes. The synergistic effect of sodium cocoyloxyethyl sulfonate molecules and benzyl triethoxysilane substances in geopolymers can effectively control the temperature changes of the slurry and reduce the shrinkage stress caused by temperature differences, thereby improving the freeze-thaw resistance and reducing the risk of cracking. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below with reference to the embodiments.
[0032] The fly ash used in the embodiments of the present invention is Class II fly ash, which complies with the national standard requirements of GB / T1596-2017 "Fly ash used in cement and concrete". The slag powder raw material used in this paper is produced in Lingshou County, Hebei Province. The S95-grade granulated blast furnace slag powder processed and produced by Tengyan Minerals complies with the national standard requirements of GB / T18046-2017 "Granulated blast furnace slag powder used in cement and concrete". Metakaolin is produced by Shuangshi Mineral Products Processing Plant in Lingshou County, Hebei Province, and complies with the national standard requirements of GB / T18046-2017 "Granulated blast furnace slag powder used in cement and concrete". The raw materials or chemical reagents, unless otherwise specified, are obtained through conventional commercial channels.
[0033] Example 1
[0034] Add 22% mixed alkali solution to fly ash, the mixed alkali solution is a solution of 18% by mass of tetra-n-butylammonium difluorotriphenyl silicate and sodium hydroxide in a ratio of 1:3, stir at 500RPM for 25min, place it in a muffle furnace, heat it to 650℃ at 15℃ / min for 80-90min, cool it to room temperature and grind it to a specific surface area of 300m 2 / kg to obtain alkali thermally activated fly ash;
[0035] Alkali-heat-activated fly ash: slag powder: metakaolin are mixed in a ratio of 5:3:2, 4% benzyltriethoxysilane is added thereto and stirred evenly, 0.3 parts of cellulose ether, 3.5 parts of FDN-C naphthalene water reducer, 0.6 parts of polyethylene glycol and 600 parts of water are mixed, and then 3.5 parts of sodium cocoyloxyethyl sulfonate are added and dispersed evenly, the rotation speed is 300RPM, the heating temperature is 80°C, and the time is 50min. Then, it is placed in an ultrasonic cleaning machine for ultrasonic dispersion for 30min, and then placed at room temperature for 2.5h to obtain a dispersion liquid, and the dispersion liquid is added at a material-liquid ratio of 6:4, first stirred slowly at 30RPM for 1min, and then stirred quickly at 150 for 4min to obtain a high-performance geopolymer.
[0036] Example 2
[0037] 18% mixed alkali solution was added to the fly ash. The mixed alkali solution was a 20% solution of tetra-n-butylammonium difluorotriphenyl silicate and sodium hydroxide in a ratio of 1:3. The mixture was stirred at 500 RPM for 20 min. The mixture was placed in a muffle furnace and heated to 700 °C at a rate of 15 °C / min for 80 min. After cooling to room temperature, the mixture was ground to a specific surface area of 320 m 2 / kg to obtain alkali thermally activated fly ash;
[0038] Alkali-heat-activated fly ash: slag powder: metakaolin are mixed in a ratio of 5:3:2, 2% benzyltriethoxysilane is added thereto and stirred evenly, 0.5 parts of cellulose ether, 2 parts of FDN-C naphthalene water reducer, 0.8 parts of polyethylene glycol and 600 parts of water are mixed, and then 2 parts of sodium cocoyloxyethyl sulfonate are added and dispersed evenly, the rotation speed is 300RPM, the heating temperature is 80°C, and the time is 60min. Then, it is placed in an ultrasonic cleaning machine for ultrasonic dispersion for 30min, and then placed at room temperature for 2h to obtain a dispersion liquid, and the dispersion liquid is added at a material-liquid ratio of 6:4, first stirred slowly at 50RPM for 1min, and then stirred quickly at 100 for 4min to obtain a high-performance geopolymer.
[0039] Example 3
[0040] Add 25% of mixed alkali solution to fly ash, the mixed alkali solution is a solution of 8% by mass of tetra-n-butylammonium difluorotriphenyl silicate and sodium hydroxide in a ratio of 1:3, stir at 500RPM for 30min, place it in a muffle furnace, heat it to 600℃ at 15℃ / min for 90min, cool it to room temperature and grind it to a specific surface area of 280m 2 / kg to obtain alkali thermally activated fly ash;
[0041] Alkali-heat-activated fly ash: slag powder: metakaolin are mixed in a ratio of 5:3:2, 5% benzyltriethoxysilane is added thereto and stirred evenly, 0.1 parts of cellulose ether, 5 parts of FDN-C naphthalene water reducer, 0.5 parts of polyethylene glycol and 600 parts of water are mixed, and then 5 parts of sodium cocoyloxyethyl sulfonate are added and dispersed evenly, the rotation speed is 300RPM, the heating temperature is 80°C, and the time is 40min. Then, it is placed in an ultrasonic cleaning machine for ultrasonic dispersion for 30min, and then placed at room temperature for 3h to obtain a dispersion liquid, and the dispersion liquid is added at a material-liquid ratio of 6:4, first stirred slowly at 10RPM for 1min, and then stirred quickly at 200 for 4min to obtain a high-performance geopolymer.
[0042] Comparative Example 1
[0043] In this comparative example, alkali excitation is carried out at room temperature, and the specific process is as follows: add 22% mixed alkali solution to fly ash, the mixed alkali solution is a solution of 18% by mass of tetra-n-butylammonium difluorotriphenyl silicate and sodium hydroxide mixed in a ratio of 1:3, first slowly stir at 30RPM for 2min, and then quickly stir at 150 for 2min;
[0044] Alkali-activated fly ash slag powder and metakaolin are mixed at a ratio of 5:3:2, 4% benzyltriethoxysilane is added thereto and stirred evenly, 0.3 parts of cellulose ether, 3.5 parts of FDN-C naphthalene water reducer, 0.6 parts of polyethylene glycol and 600 parts of water are mixed, and 3.5 parts of sodium cocoyloxyethyl sulfonate are added and dispersed evenly, the rotation speed is 300RPM, the heating temperature is 80°C, and the time is 50min. Then, it is placed in an ultrasonic cleaning machine for ultrasonic dispersion for 30min, and then placed at room temperature for 2.5h to obtain a dispersion liquid, and the dispersion liquid is added at a material-liquid ratio of 6:4, first stirred slowly at 30RPM for 1min, and then stirred quickly at 150 for 4min to obtain a high-performance geopolymer.
[0045] Comparative Example 2
[0046] In this comparative example, tetra-n-butylammonium difluorotriphenylsilicate is water glass, and the rest is the same as in Example 1.
[0047] Comparative Example 3
[0048] The dosage of tetra-n-butylammonium difluorotriphenyl silicate in this comparative example is different, specifically: 22% of a mixed alkali solution is added to the fly ash, wherein the mixed alkali solution is a solution of 18% by mass of tetra-n-butylammonium difluorotriphenyl silicate and sodium hydroxide in a 1:1 ratio, stirred at 500RPM for 25min, placed in a muffle furnace, heated to 650℃ at 15℃ / min for 80-90min, cooled to room temperature and ground to a specific surface area of 300m 2 / kg; the rest is the same as in Example 1.
[0049] Comparative Example 4
[0050] The dosage of tetra-n-butylammonium difluorotriphenyl silicate in this comparative example is different, specifically: 22% of a mixed alkali solution is added to the fly ash, wherein the mixed alkali solution is a solution of 18% by mass of tetra-n-butylammonium difluorotriphenyl silicate and sodium hydroxide in a ratio of 1:5, stirred at 500RPM for 25min, placed in a muffle furnace, heated to 650℃ at 15℃ / min for 80-90min, cooled to room temperature and ground to a specific surface area of 300m 2 / kg; the rest is the same as in Example 1.
[0051] Comparative Example 5
[0052] In this comparative example, no benzyltriethoxysilane was added, and the rest was the same as in Example 1.
[0053] Comparative Example 6
[0054] In this comparative example, benzyltriethoxysilane is monosilane, and the rest of the implementation manner is the same as Example 1.
[0055] Comparative Example 7
[0056] In this comparative example, the amount of benzyltriethoxysilane added is different, specifically: alkali-heat-activated fly ash: slag powder: metakaolin is mixed in a ratio of 5:3:2, 8% benzyltriethoxysilane is added thereto and stirred evenly, 0.3 parts of cellulose ether, 3.5 parts of FDN-C naphthalene water reducer, 0.6 parts of polyethylene glycol and 600 parts of water are mixed, and then 3.5 parts of sodium cocoyloxyethyl sulfonate are added and dispersed evenly, the rotation speed is 300RPM, the heating temperature is 80°C, the time is 50min, and then it is placed in an ultrasonic cleaning machine for ultrasonic dispersion for 30min, and then placed at room temperature for 2.5h to obtain a dispersion liquid, and the dispersion liquid is added at a material-liquid ratio of 6:4, first slowly stirred at 30RPM for 1min, and then quickly stirred at 150 for 4min to obtain a high-performance geopolymer; the remaining implementation methods are the same as Example 1.
[0057] Comparative Example 8
[0058] In this comparative example, the amount of benzyltriethoxysilane added is different, specifically: alkali-heat-activated fly ash: slag powder: metakaolin is mixed at a ratio of 5:3:2, 1% benzyltriethoxysilane is added thereto and stirred evenly, 0.3 parts of cellulose ether, 3.5 parts of FDN-C naphthalene water reducer, 0.6 parts of polyethylene glycol and 600 parts of water are mixed, and then 3.5 parts of sodium cocoyloxyethyl sulfonate are added and dispersed evenly, the rotation speed is 300RPM, the heating temperature is 80°C, the time is 50min, and then it is placed in an ultrasonic cleaning machine for ultrasonic dispersion for 30min, and then placed at room temperature for 2.5h to obtain a dispersion liquid, the dispersion liquid is added at a material-liquid ratio of 6:4, first stirred slowly at 30RPM for 1min, and then stirred quickly at 150 for 4min to obtain a high-performance geopolymer; the remaining implementation methods are the same as Example 1.
[0059] Comparative Example 9
[0060] In this comparative example, sodium cocoyloxyethyl sulfonate is not added; the remaining implementation methods are the same as those in Example 1.
[0061] Comparative Example 10
[0062] In this comparative example, sodium cocoyloxyethyl sulfonate is cetyltrimethylammonium bromide; the remaining implementation methods are the same as those in Example 1.
[0063] Comparative Example 11
[0064] In this comparative example, the addition amount of sodium cocoyloxyethyl sulfonate is different, specifically: alkali-heat-activated fly ash: slag powder: metakaolin is mixed in a ratio of 5:3:2, 4% benzyltriethoxysilane is added thereto and stirred evenly, 0.3 parts of cellulose ether, 3.5 parts of FDN-C naphthalene water reducer, 0.6 parts of polyethylene glycol and 600 parts of water are mixed, and then 8 parts of sodium cocoyloxyethyl sulfonate are added and dispersed evenly, the rotation speed is 300RPM, the heating temperature is 80°C, the time is 50min, and then it is placed in an ultrasonic cleaning machine for ultrasonic dispersion for 30min, and then placed at room temperature for 2.5h to obtain a dispersion liquid, and the dispersion liquid is added at a material-liquid ratio of 6:4, first stirred slowly at 30RPM for 1min, and then stirred quickly at 150 for 4min to obtain a high-performance geopolymer; the rest is the same as Example 1.
[0065] Comparative Example 12
[0066] In this comparative example, the addition amount of sodium cocoyloxyethyl sulfonate is different, specifically: alkali-heat-activated fly ash: slag powder: metakaolin is mixed in a ratio of 5:3:2, 4% benzyltriethoxysilane is added thereto and stirred evenly, 0.3 parts of cellulose ether, 3.5 parts of FDN-C naphthalene water reducer, 0.6 parts of polyethylene glycol and 600 parts of water are mixed, and then 1 part of sodium cocoyloxyethyl sulfonate is added and dispersed evenly, the rotation speed is 300RPM, the heating temperature is 80°C, the time is 50min, and then it is placed in an ultrasonic cleaning machine for ultrasonic dispersion for 30min, and then placed at room temperature for 2.5h to obtain a dispersion liquid, and the dispersion liquid is added at a material-liquid ratio of 6:4, first stirred slowly at 30RPM for 1min, and then stirred quickly at 150 for 4min to obtain a high-performance geopolymer; the rest is the same as Example 1.
[0067] Test 1:
[0068] The conductive ultra-high performance geopolymer was prepared into a test block with a size of 40*40*160m, and after 24h of laboratory curing, the block was demoulded and cured to 28d, and then its flexural strength and compressive strength were tested. The test results are shown in Table 1.
[0069] Table 1 Strength determination
[0070] Group Flexural strength(MPa) Flexural strength(MPa) Example 1 153.4 31.3 Example 2 152.5 30.8 Example 3 153.2 30.6 Comparative Example 1 142.8 20.3 Comparative Example 2 143.9 21.6 Comparative Example 3 150.7 28.5 Comparative Example 4 146.5 25.9 Comparative Example 5 151.3 27.8 Comparative Example 6 152.2 27.5 Comparative Example 7 151.6 28.2 Comparative Example 8 150.9 28.3 Comparative Example 9 147.2 28.0 Comparative Example 10 146.5 27.9 Comparative Example 11 150.4 28.5 Comparative Example 12 148.3 28.4
[0071] Test 2: Determination of coagulation, viscosity and fluidity
[0072] The initial setting time and final setting time of the high performance geopolymers in Examples 1-3 and Comparative Examples 1-12 were tested.
[0073] Marsh funnel viscosity test:
[0074] The Marsh funnel viscometer is also called a cone Marsh funnel, which consists of a six-hole (16-mesh) screen and a 1000mL measuring cup. The upper diameter of the cone is 152mm, the lower diameter of the cone and the diameter of the flow tube are 4.76mm, the cone length is 305mm, the total length of the funnel is 356mm, and the funnel volume below the screen bottom is 1500mL;
[0075] Determination method: Before measuring the viscosity, first clean the flow cone with water, stir the geopolymer slurry in Examples 1-3 and Comparative Examples 1-12 to be measured, and then inject the slurry (1725mL±5mL slurry) into the flow cone (wall thickness 3mm) with a measuring cup, and plug the cone mouth (inner diameter 13mm) with a rubber plug to prevent the slurry from flowing out. When measuring, place the measuring cup under the outflow port, remove the rubber plug, and start the stopwatch at the same time. When the slurry flows out, press the stopwatch again and record the time when the slurry flows out. This is the viscosity of the slurry, and its unit is expressed in seconds. Under specified conditions, the time required for a certain volume of slurry to flow out is defined as the viscosity of the grouting material, and the unit is s.
[0076] Fluidity: Fluidity is measured according to the relevant provisions of GB / T8077-2012 Test Method for Homogeneity of Concrete Admixtures. After the geopolymer slurries of Examples 1-3 and Comparative Examples 1-12 are prepared, they are injected into a truncated cone circular mold fluidity tester (with specifications of upper opening 36mm, lower opening 60mm, and height 60mm) placed on a square glass plate of L=600mm (the surface has been wetted), and then lifted vertically and the timing is started. After 30s, the diffusion opening of the slurry is measured with a ruler. Each group of slurries is measured three times, and the average value of the three times is taken as the fluidity. The results are shown in Table 2.
[0077] Table 2 Results of determination
[0078] Group Initial setting time (min) Final setting time (min) Viscosity(s) Fluidity(mm) Example 1 42 48 45 298 Example 2 45 52 43 295 Example 3 45 53 44 296 Comparative Example 1 54 66 38 287 Comparative Example 2 56 63 36 289 Comparative Example 3 52 62 40 290 Comparative Example 4 54 58 39 285 Comparative Example 5 72 86 32 242 Comparative Example 6 69 85 34 247 Comparative Example 7 56 68 39 292 Comparative Example 8 60 73 37 282 Comparative Example 9 71 85 33 255 Comparative Example 10 65 78 34 262 Comparative Example 11 54 64 40 291 Comparative Example 12 58 69 38 284
[0079] Test 3: Freeze-thaw resistance test
[0080] The polymers in Examples 1-3 and Comparative Examples 1-12 were injected into a mold (70.7mm*70.7mm*70.7mm cubic mold), with 10 molds per group. After curing for 24 hours, the molds were removed, and the demoulding samples were labeled and cured in a standard curing room for 28 days. 2 days before the freeze-thaw test, the test block was taken out of the curing room and placed in water at room temperature. After being completely soaked for two days, it was taken out, wiped dry with wool, weighed, and pressure tested. After recording the weighing data and compressive strength data, the freeze-thaw specimens were placed in a freeze-thaw machine for freeze-thaw tests. The freeze-thaw temperature range was set at -15°C to 15°C, the freeze-thaw number was set to 100 times, and the thawing and freezing times were both 4 hours. After the freeze-thaw cycle number was reached, the specimens were taken out for weighing and pressure testing, and the mass loss rate was calculated. The results are shown in Table 3 below.
[0081] Mass loss rate after 100 freeze-thaw cycles = (mean mass after 100 freeze-thaw cycles - mean initial mass) / mean initial mass
[0082] Table 3 Freeze-thaw resistance determination
[0083] Sample Group Initial mass mean (g) Average mass after 100 freeze-thaw cycles (g) Mass loss rate after 100 freeze-thaw cycles (%) Example 1 692 685 1.01 Example 2 703 695 1.14 Example 3 701 692 1.28 Comparative Example 1 689 674 2.18 Comparative Example 2 692 675 2.46 Comparative Example 3 695 681 2.01 Comparative Example 4 700 685 2.14 Comparative Example 5 698 668 4.29 Comparative Example 6 695 674 3.02 Comparative Example 7 688 676 1.74 Comparative Example 8 689 672 2.47 Comparative Example 9 694 668 3.75 Comparative Example 10 695 670 3.60 Comparative Example 11 699 683 2.43 Comparative Example 12 703 682 2.99
Claims
1. A method for preparing a geopolymer for road grouting reinforcement, characterized in that: Add 18-25% mixed alkali solution to fly ash, stir at 500RPM for 20-30min, place it in a muffle furnace, heat it to 600-700℃ at 15℃ / min for 80-90min, cool it to room temperature and grind it to a specific surface area of 280-320m 2 / kg to obtain alkali thermally activated fly ash; Alkaline thermally activated fly ash: slag powder: metakaolin in a ratio of 5:3:2, add 2-5% of silane material and stir evenly, then add dispersion liquid in a material-liquid ratio of 6:4, first stir slowly at 10-50RPM for 1 minute, then stir quickly at 100-200 for 4 minutes to obtain high-performance geopolymer; The mixed alkali solution is a solution in which tetra-n-butylammonium difluorotriphenylsilicate and sodium hydroxide are mixed in a ratio of 1:3 with a mass fraction of 8-20%.
2. The method for preparing a geopolymer for road grouting reinforcement according to claim 1, characterized in that: The silane material is benzyltriethoxysilane.
3. The method for preparing a geopolymer for road grouting reinforcement according to claim 1, characterized in that: The dispersion liquid is prepared by mixing 0.1-0.5 parts of cellulose ether, 2-5 parts of FDN-C naphthalene water reducer, 0.5-0.8 parts of polyethylene glycol and 600 parts of water, and then adding 2-5 parts of a surfactant to disperse evenly, rotating at 300RPM, heating at 80°C for 40-60 minutes, and then placing it in an ultrasonic cleaning machine for ultrasonic dispersion for 30 minutes, and then placing it at room temperature for 2-3 hours to obtain a dispersion liquid.
4. The method for preparing a geopolymer for road grouting reinforcement as claimed in claim 3, characterized in that: The surfactant is sodium cocoyloxyethyl sulfonate.
5. An application of a geopolymer for road grouting reinforcement obtained by any preparation method of claims 1 to 4, characterized in that: application include: (1) Divide the construction area according to the defect detection results and design, and stake out the construction area on site according to the designed grouting drilling hole layout diagram, determine the drilling hole positions, mark the positions with spray paint, and mark the drilling depth; (2) Use a 20mm diameter drill bit to drill holes according to the hole layout. Keep the drill rig vertical to the road surface during drilling to avoid left and right shaking. After the drill rod reaches the designed depth, pull the drill rod up and down to discharge the powder in the hole, move to the next hole position and repeat the step; (3) After drilling is completed, check the hole depth. If the depth is not enough, deepen it again to reach the designed hole depth. During the drilling process, use a cleaning tool to clean the powder around the hole, use a special container to hold the powder, and dispose of it centrally after the construction is completed; (4) Grouting the prepared geopolymer grouting material with a grouting pressure of 0.6 MPa, a grouting hole spacing of 150 cm, a grouting volume of 70-120 kg / m2, and a grouting depth of 0.8-1.2 m; (5) After grouting is completed, quickly close the grouting hole with a plug, rinse off the grout spilled on the road surface, and clean the road surface; (6) After the grouting is completed, it must be cured for 6 hours before subsequent paving construction can be carried out.
Citation Information
Patent Citations
Calcium-base geopolymer and preparation method thereof
CN105621907A
Air-entrapping expanded type geopolymer for grouting reinforcement of roads
CN108546016A
Method for preparing high-strength mortar and concrete by using low-quality fly ash
CN108751917A
Cement concrete pavement rapid repair material and preparation method thereof
CN112723801A
Rapidly-hardened high-strength fly ash geopolymer material and preparation method thereof
CN113416025A
Cited By
Early-strength high-fluidity geopolymer grouting material and preparation method thereof
CN119591354A